Transportation infrastructure and economic growth in Sub-Saharan region - JABU, Alex (KDI School, 2015)
This paper investigates the role of road infrastructure on economic development in Sub-Saharan African Region. We use data from 1990 to 2012 covering 48 countries. The study finds that Road Infrastructure does not contribute to the economic development of a country.
Thesis(Master) --KDI School:Master of Public Policy,2015